تطوير منهج اللغة العربية ببيسنترين وادي العلوم الإسلامي على أساس التفقه في الدين وثنائية اللغة - Al Barokah, Andyani Julinda Anggraeni; Mahfudh , Sahal; Subhan, Ali (STAINI Press, 2025)
Pesantren are divided into two main categories, namely traditional and modern pesantren. Traditional pesantren use traditional methods that focus on developing receptive skills, while modern pesantren use modern methods that focus on developing productive skills. Pesantren Wadil Ulum Pati integrates traditional methods and modern methods. This pesantren uses traditional methods such as Bandongan and Sorogan to develop receptive skills, as well as modern methods that support the development of productive skills through the Arabic curriculum system. This study aims to analyze the background, form of development, and relevance of the Arabic curriculum in the pesantren. The research method used a qualitative approach with a case study design. Data were obtained through interviews, documents, and questionnaires, then analyzed using the Miles and Huberman model. Data validity was tested through triangulation of techniques and sources, as well as expert validation. The results showed that curriculum development is based on philosophical, socio-cultural, religious, scientific foundations, as well as community needs. Philosophical and religious foundations are the dominant factors. Development is carried out in the aspects of objectives, materials, media, strategies, methods, learning activities, and evaluation. In terms of relevance, this curriculum is not only theoretical but also proven practical through various successes. This research is expected to contribute as a reference for Arabic curriculum development in other pesantren in Indonesia.